Transcriptomic and Physiological Analysis Reveals the Responses to Auxin and Abscisic Acid Accumulation During Vaccinium corymbosum Flower Bud and Fruit Development - Liu, Liangmiao; Zheng, Yiqi; Feng, Shiji; Yu, Lei; Li, Yongqiang; Zong, Yu; Chen, Wenrong; Liao, Fanglei; Yang, Li; Guo, Weidong (Frontiers in Plant Science, 2022)
Blueberry (Vaccinium corymbosum) is reputed as a rich source of health-promoting phytonutrients, which contributes to its burgeoning consumer demand and production. However, blueberries are much smaller and have lower yields than most domesticated berries, and the inherent regulatory mechanisms remain elusive. In this study, the cytological and physiological changes, as well as comparative transcriptomic analysis throughout flower and fruit development in the southern highbush blueberry cultivar 'O'Neal' were performed. 'O'Neal' hypanthium and fruit exhibited a distinctive cell proliferation pattern, and auxin accumulation was unusual throughout development, while abscisic acid (ABA) levels rapidly increased in association with anthocyanin accumulation, total phenolic reduction and fruit maturation. Transcriptomic data showed that many differentially expressed genes (DEGs) were specifically expressed at each flower bud and fruit developmental stage. Further weighted gene co-expression network analysis (WGCNA) revealed numerous DEGs that correlated with the cell numbers of outer mesocarp and columella, showed two distinctive expression patterns. Most of the DEGs involved in auxin transport and signal transduction were upregulated, and this upregulation was accompanied by cell expansion, and flower bud and fruit development. However, individual members of VcIAA9 and VcSAUR50 families might be insensitive to auxin, suggesting that these genes play a distinctive role in the growth and development of blueberry fruits. These results will support future research to better understand the flower and fruit development of southern highbush blueberry.